Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Simplify and then solve the equation. Input the solution as a fraction.

[tex]
\begin{array}{l}
2x - 3(4x - 1) = 17 + 3x \\
\end{array}
\]


Sagot :

Certainly! Let's solve the equation step-by-step:

Given the equation:
[tex]\[ 2x - 3(4x - 1) = 17 + 3x \][/tex]

First, distribute the [tex]\(-3\)[/tex] on the left side:
[tex]\[ 2x - 3 \cdot 4x + 3 \cdot 1 = 17 + 3x \][/tex]
[tex]\[ 2x - 12x + 3 = 17 + 3x \][/tex]

Combine like terms on the left side:
[tex]\[ (2x - 12x) + 3 = 17 + 3x \][/tex]
[tex]\[ -10x + 3 = 17 + 3x \][/tex]

Next, isolate the variable [tex]\( x \)[/tex] by moving all [tex]\( x \)[/tex] terms to one side of the equation. Subtract [tex]\( 3x \)[/tex] from both sides:
[tex]\[ -10x + 3 - 3x = 17 + 3x - 3x \][/tex]
[tex]\[ -13x + 3 = 17 \][/tex]

Now, subtract 3 from both sides to isolate the term with [tex]\( x \)[/tex]:
[tex]\[ -13x + 3 - 3 = 17 - 3 \][/tex]
[tex]\[ -13x = 14 \][/tex]

Finally, solve for [tex]\( x \)[/tex] by dividing both sides by [tex]\(-13\)[/tex]:
[tex]\[ x = \frac{14}{-13} \][/tex]
[tex]\[ x = -\frac{14}{13} \][/tex]

Therefore, the solution to the equation is:
[tex]\[ x = -\frac{14}{13} \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.